Impurity-bearing ferrihydrite nanoparticle precipitation/deposition on quartz and corundum. Issue 1 (27th November 2017) - Dai, Chong; Liu, Juanjuan; Hu, Yandi
Abstract : During ferrihydrite precipitation, metal ions can be sequestered in it to form impurity-bearing ferrihydrite (IBF). Abstract : During ferrihydrite precipitation, metal ions can be sequestered in it to form impurity-bearing ferrihydrite (IBF). Using grazing-incidence small-angle X-ray scattering (GISAXS), heterogeneous precipitation/deposition of pure and IBF nanoparticles on quartz (SiO2 ) and corundum (Al2 O3 ) was quantified in 0.1 mM Fe 3+ solutions in the absence and presence of 1 mM Mn 2+ or Al 3+ (pH = 3.8 ± 0.1). The impurity ions (Mn and Al) greatly affected ferrihydrite nanoparticle precipitation/deposition on substrates. On SiO2, ferrihydrite nanoparticle precipitation/deposition was promoted in the presence of Mn but was inhibited in the presence of Al. On Al2 O3, Mn- and Al-bearing ferrihydrite nanoparticle precipitation/deposition was slower than for pure ferrihydrite. Compared with on SiO2, pure and IBF nanoparticle precipitation/deposition on Al2 O3 was significantly inhibited. To understand the mechanisms, interactions among impurity ions, substrates, and precipitates were explored. Surface enrichment of Mn and Al on precipitates was found to increase the zeta potential of ferrihydrite nanoparticles. The changes in surface charges of the precipitates and substrates affected heterogeneous IBF precipitation/deposition significantly. The rates and mechanisms of heterogeneous IBF precipitation/deposition provided here can help predict pollutant transport and design catalyst synthesis.